Pengembangan Profesionalisme Guru melalui Penulisan Karya Tulis Ilmiah bagi Guru Profesional di SMK Muhammadiyah 1 Blora - Ulum, M Nurul (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2017)
Teacher as professional person has function, role and position, are very important in achieving national education vision for creating Indonesian smart and competitive people. Teacher must develop profession getting dignity. One of teacher's professional development form is to academic writing. Yet inreal situation the teacher's activities still focus on both vision and mission of education and teaching. While the scientific vision and mission in written forms and publication are often ignored. The research uses qualitative approach with descriptive method it describes the result of the research gained from interview, document analysis, participation observation and focus group discussion. The results of research show that the causes of the teacher's difficulties in academic writing involve: a) teacher's low motivation, b) having no sparitime, c) lack of comprehending about the writing technique, d) difficulty of finding out the data, e) not familiar with modern technology, f) not having reference books, g) the existence of the writing services of scientific opus, h) lack of role of MGMP activities in socializing academic writing, and i) lack of socialization from school or educational institution. Based on the research result is recommended to the headmaster in order to do on going workshop, adding the library's reference books, holding computer training, applying managerial pattern ( reward and punishment), monitoring MGMP activities, lastly doing control and observation of the evaluator's team activities related to teacher's work and the ongoing professional development's team. Keywords: professionalism, academic writing, professional teacher